Carriage of antimicrobial resistance genes in Escherichia coli of bovine origin - Ozbey, G.; Tanriverdi, E. S.; Acik, M. N.; Kalin, R.; Otlu, B.; Zigo, F. (Polska Akad Nauk, Polish Acad Sciences, Univ Warmia & Mazury Olsztyn, 2024)
The present study aimed to search for the presence of the plasmid-mediated antimicrobial resistance genes in 106 Escherichia coli (E. coli) isolates from a total of 240 fresh fecal samples collected from 12 private cattle farms in Bingol province of East Turkey from November 2021 to January 2022. In those colistin-resistant E. coli (mcr-1 to-9), the major carbapenemase ( bla OXA-48 , bla NDM-1 , bla IMP, bla VIM, and bla KPC ), beta-lactamase (blaTEM-1, bla CTX-M and bla SHV-1 ) and OXA-48 like beta- lactamase ( bla OXA-162 , bla OXA-163 , bla OXA-181 , bla OXA-204 and bla OXA-232 ) resistance genes were searched for determined a multiplex polymerase chain reaction (PCR) method and Next-generation sequencing (NGS)- PCR Amplicons with Nanopore Technology. Only the mcr-4 gene was found in one isolate and the remaining genes (mcr-1-9) were not shown in all E. coli isolates from cattle. The minimal inhibitory concentration (MIC) to colistin was detected in mcr-4 positive E. coli isolates using broth microdilution. We assessed the antimicrobial susceptibilities of mcr-4 positive E. coli isolates using the Kirby-Bauer disk diffusion method. E coli isolate was detected as negative for carbapenemase and OXA-48 like beta-lactamase resistance genes and positive for beta-lactamase. In addition, E. coli isolates carrying mcr-4 were more resistant to colistin. Antimicrobial susceptibility testing using the disk diffusion assay indicated that all 106 E. coli isolates (100%) were sensitive to AMK, 105 E. coli isolates (99.1%) exhibited sensitivity to imipenem, meropenem and doripenem, and 1 E. coli isolate (0.9%) had intermediate resistance to imipenem, meropenem and doripenem; It was observed that all strains (100%) were resistant to cefotaxime. E. coli isolates are resistant to ampicillin (95.3%), amoxicillin/clavulanic acid (95.3%), cefepime (14.2%), cefixime (19.8%), cephalexin (74.5%), gentamicin (42.5%), kanamycin (37.7%), streptomycin (69.8%), tetracycline (80.2%), ciprofloxacin (60.4%), norfloxacin (13.2%), chloramphenicol (59.4%) and trimethoprim/sulfamethoxazole (68.9%). When we investigated the sequence in the Blast database, the genome of the E. coli isolate indicated high similarity with the mcr-4 sequences. To our knowledge, this is the first report investigating on the mcr-4 gene in E. coli identified from cattle in Turkey. Our results highlighted that cattle might be a potential risk in transmitting mcr genes.
Keywords: cattle; Escherichia coli; mcr; multiplex PCR; NGS